“Community 101 for researchers”: an online training program to build capacity for ethical community-engaged research with Native Hawaiians and Pacific Islanders - Chung-Do, Jane J.; Scott, Samantha Keaulana; Jones, Bradley R.; Look, Mele A.; Taira, Deborah A.; Palafox, Neal A.; Farrar, Kamahanahokulani; Mau, Marjorie K. Leimomi M. (Frontiers in Public Health, 2024)
To address the history of unethical research and community distrust in research among Native Hawaiian and Pacific Islander communities, we developed the “Community 101 for Researchers” training program, which was launched in 2014 to enhance the capacity of researchers to engage in ethical community-engaged research. The purpose of this paper is to describe the development of this training program as well as its reach and feedback from participants. The Community 101 training program is a self-paced, 2-h online training program featuring community-engaged researchers from the University of Hawai‘i and their longstanding community partners. Throughout the five modules, we highlight the historical context of Native Hawaiians and Pacific Islander populations in Hawai‘i related to research ethics and use examples from the community as well as our own research projects that integrate community ethics, relevance, benefits, and input. To determine reach and gather participant feedback on the training, we extracted data from the user accounts. The training has been completed by 697 users to-date since its launch. Despite very little advertisement, an average of nearly 70 users have completed the Community 101 Program each year. The majority of the participants were located in Hawai‘i though participants were also from other states and territories in the US, and international locations. The majority of participants were from universities in Hawai‘i in 51 different departments demonstrating multidisciplinary relevance of the program's training. The general feedback from the 96 participants who completed an optional anonymous evaluation survey given at the end of the training was positive. The “Community 101 for Researchers” Training program is an accessible and relevant tool that can be used to advance ethical community engaged research, specifically with Native Hawaiian and Pacific Islander communities.